(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
In this work, many samples have been prepared by adding Antimony Trioxide (Sb2O3) to the polyvinyl alcohol-poly ethylene glycol (PVA-PEG). The effect of the Sb2O3 added as a filler with different weight percentages on the A.C electrical properties have been investigated. The samples were prepared as films by solution cast technique. The experimental results of the A.C electrical properties show that the dielectric constant increase with the increasing frequency of applied electrical field and concentration of the Antimony Trioxide. Dielectric loss decrease with the increasing the frequency, while it increases with the increase of the concentration of the Antimony Trioxide. The A.C electrical conductivity increase with increasing the Antimony Trioxide contain and frequency for the composition.